«Ջրաբերդ» ամրոցը - Սարգսյան, Սլավա (ԱրՊՀ հրատ․)
На основе сопоставления исторических источников и результатов исследования на месте описывается одна из известных крепос-тей Хачена, которая оставила значительный след в истори и Арцаха. Вместе с краткой историей крепости и описанием основных строений комплекса, показаны роль и значение этого единственного в своем роде оборонительного узла в нижней долине реки Тартар. Based on the comparison of historic sources and research results on the spot one of the most famous fortresses of Khachen is described which left a significant mark in the history of Artsakh. Together with the brief history of the fortress and the description of the main buildings of the complex, the role and importance of this unique defensive unit in the lower valley of Tartar are shown.
Keywords: Արցախ; Հնագիտություն